Using Semantic Features to Detect Spamming in Social Bookmarking Systems - Madkour, Amgad; Hefni, Tarek; Hefny, Ahmed; Refaat, Khaled S. (ECML PKDD, 2008)
Collaborative software is gaining pace as a vital means of information sharing between users. This paper discusses one of the key challenges that affect such systems which is identifying spammers. We discuss potential features that describe the system’s users and illustrate how we can use those features in order to determine potential spamming users through various machine learning models.